2016
DOI: 10.1080/08959420.2016.1163652
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Experienced at Age 100: Findings From the Fordham Centenarian Study

Abstract: This article examines the challenges experienced by very old individuals and their consequences for well-being and mental health. In order to capture unique issues experienced in very old age, 75 participants of the population-based Fordham Centenarian Study answered open-ended questions on everyday challenges. Theme-based coding was then used to categorize and quantify responses. The challenges mentioned most often were challenges faced in the functional (e.g., physical health/activities of daily living restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Although the networks of the oldest old were small, their ties with family members, professionals, friends, and neighbours were strong because of regular contact. Such regular contact provides opportunities for social exchange with a small, yet regularly present, group of informal and formal caregivers (Jopp et al, 2016). Despite their small networks, the oldest old felt they had a moral obligation to contribute to society.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the networks of the oldest old were small, their ties with family members, professionals, friends, and neighbours were strong because of regular contact. Such regular contact provides opportunities for social exchange with a small, yet regularly present, group of informal and formal caregivers (Jopp et al, 2016). Despite their small networks, the oldest old felt they had a moral obligation to contribute to society.…”
Section: Discussionmentioning
confidence: 99%
“…These people also tend to avoid having any conflicts in regard to relationships and do not wish to compare themselves to others (Darviri et al, 2009) when the oldest old accept themselves and their lives, both the good and the bad, they become comfortable being themselves, and find peace and happiness. Consequently, the oldest old are mostly satisfied with their present lives (Darviri et al, 2009; Eloranta et al, 2012; Zeng et al, 2017), and their happiness is not influenced by their physical limitations (Jopp et al, 2016). Analysis of the developmental course of emotional experience has revealed that as people age, overall emotional well-being becomes more positive and stable, and that individuals who are positive are more likely to live longer than those who commonly feel negative emotions (Carstensen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More focused studies have also determined the factors relating to happiness in the elderly. Aside from declining physical health the main risk factors that were identified are principally psychosocial and included social isolation and the death of close friends and loved ones, especially family members 16. This is reinforced by other studies which have shown that the elderly place more emphasis on close relationships such as those with family members than on maintaining wider social networks 14.…”
Section: The Best Possible Life and Extending Lifespanmentioning
confidence: 97%